Assessing the responses of wheat roots and shoots to variations in soil water, temperature and CO2 concentration - Khalil, Aveen (2017)
Wheat (Triticum aestivum L.) is one of the most important cereal crops in the world. In order to meet the food requirements of the current trend in population growth, enhancement in wheat production and yield are urgently needed. Water and temperature stress are major constraints to wheat production and subsequently food security in the context of climate change. Plant growth is affected by both above- and belowground environmental conditions and increasing atmospheric CO2 concentrations have been reported to enhance growth and yield of most agricultural crops. The responses of wheat roots and shoots to variations in soil water, temperature and CO2 concentration were studied in this research. X-ray Computed Tomography (X-ray CT) was used to visualise and quantify the behaviour of roots grown in soil under contrasting conditions for water content, temperature and CO2 concentration. Photosynthesis, stomatal conductance and transpiration were also measured to examine the shoot behaviour under the same environmental conditions. The results showed that total root volume (after 14 days) under the combined effect of elevated CO2 and temperature and mean root diameter for all experiments increased significantly with increasing water stress. However, total root volume decreased significantly under the effect of water stress independently and in combination with elevated CO2 and temperature. Mean root diameter also decreased significantly under repeated soil wetting and drying cycles. Total root volume and mean root diameter at 400 ppm CO2 growth was significantly greater than at 800 ppm CO2 growth at 14 days, while it was significantly lower at 30 days. Photosynthesis, stomatal conductance and transpiration decreased significantly by increasing water stress. Photosynthesis at 800 ppm CO2 was significantly greater than at 400 ppm CO2 while stomatal conductance and transpiration at 400 ppm CO2 were significantly greater. The elevated CO2 enhanced root architecture system and promoted photosynthesis. This research has demonstrated how the interacting variables of water, temperature and CO2 impact on the growth of wheat plants roots and shoots supporting the development of new management strategies for wheat to assist with the food security challenge under a changing environment.